Kecerdasan Emosional dan Dukungan Atasan sebagai Determinan Komitmen Perawat di Era Pandemi COVID-19 - Asra Dewi; Rr. Tutik Sri Hariyati; Kuntarti Kuntarti; Hanny Handiyani; Laurentia Dewi (Journal of Telenursing (JOTING), 2021)
This study aims to identify the determinants of nurses' commitment to providing nursing care in the era of the COVID-19 pandemic. The research design used a cross-sectional approach involving 221 nurses and team leaders at two public hospitals in West Kalimantan. The results showed that the determinants of nurses' commitment in providing nursing care in the era of the COVID-19 pandemic were emotional intelligence (p=0.001) and superior support (p=0.009). Each additional emotional intelligence point and support from superiors will increase nurses' commitment to providing nursing care by 0.239 times and 0.125 times, respectively. Factors of age, length of work, gender, education level, marital status, and work unit room were not related to nursing commitment (p > 0.05). In conclusion, the factor most related to nurses' responsibility in providing nursing care in the era of the COVID-19 pandemic is emotional intelligence. Keywords: Nursing Care, COVID-19, Superior Support, Emotional Intelligence, Nurse Commitment